2004
DOI: 10.1038/oby.2004.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internet Support on the Long‐Term Maintenance of Weight Loss

Abstract: Results: There were no significant differences among the groups in weight loss (mean Ϯ SD) from baseline to 18 months (7.6 Ϯ 7.3 kg vs. 5.5 Ϯ 8.9 kg vs. 5.1 Ϯ 6.5 kg, p ϭ 0.23 for the IS, M-IPS, and F-IPS, respectively). Discussion: Participants assigned to an internet-based weight maintenance program sustained comparable weight loss over 18 months compared with individuals who continued to meet face-to-face. Therefore, the internet appears to be a viable medium for promoting long-term weight maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
247
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(256 citation statements)
references
References 34 publications
5
247
1
3
Order By: Relevance
“…The way the subjects received the guidelines (by mail or internet) nor the kind of guidelines they received were related to WM. In this respect, Harvey-Berino et al 45,46 reported similar results. Comparing dietary disciplined subjects and activity-related disciplined subjects, dietary disciplined subjects showed significantly better WM after weight loss compared to activity-related disciplined subjects.…”
Section: Discussionsupporting
confidence: 72%
“…The way the subjects received the guidelines (by mail or internet) nor the kind of guidelines they received were related to WM. In this respect, Harvey-Berino et al 45,46 reported similar results. Comparing dietary disciplined subjects and activity-related disciplined subjects, dietary disciplined subjects showed significantly better WM after weight loss compared to activity-related disciplined subjects.…”
Section: Discussionsupporting
confidence: 72%
“…While government-led telehealth initiatives tend to focus on video conferencing, a number of small studies and pilot projects delivering health services via the Internet have been reported in patients with breast cancer (21,22), asthma (23), chronic obstructive pulmonary disease (24,25), diabetes (26)(27)(28)(29)(30)(31)(32), lung transplantation (33), overweight (34)(35)(36)(37)(38)(39)(40), smokers (41), chronic heart failure (25,(42)(43)(44) and CVD (45)(46)(47)(48). These studies demonstrated that patients were willing to enter self-measured data online and communicate with health care providers via e-mail and/or chat/video conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…One study 25 used it as a substitute for face-to-face counseling. The remaining six studies 12,[21][22]29,32,37 investigated the effectiveness of the Internet as either an adjunct or substitute. In five studies, the aim of the lifestyle modification was weight maintenance, whereas it was initial weight loss in the remaining 18 studies.…”
Section: Data Synthesismentioning
confidence: 99%